Penerapan Sistem Informasi Stok Barang Berbasis Web untuk Meningkatkan Efisiensi Manajemen Persediaan di Fortuna Furniture - Aditya Maulana Afrizal; Pratomo Setiaji (Lembaga Pengembangan Kinerja Dosen, 2025)
Fortuna Furniture still manages its inventory manually, which causes many problems, including delayed reports, inaccurate information, and the potential for lost records. These issues affect the quality of decision-making and operational efficiency. This service aims to build a web-based inventory information system that improves speed, accuracy, and integration in inventory management. The system development process follows the Waterfall model SDLC approach, with requirements analysis, design, implementation, and testing supported by interviews, observation, and documentation. The results of the activity show that the developed system can reduce input errors, speed up the process of recording incoming and outgoing goods, and enable real-time stock monitoring. Additionally, the report generation process becomes more efficient and easier for management to access. Overall, the use of this information system significantly improved the efficiency of Fortuna Furniture's inventory management and demonstrated the importance of digitalization in helping businesses run more smoothly.